Clinical Supervision's Role in Improving Teachers' Teaching Skills in Online Learning - Wulandari, Dwi; Vivekanantharasa, Raveenthiran; Fauzan, Ahmad (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2022)
The purpose of this study is to describe the role of clinical supervision in improving teachers' teaching abilities during online learning. This study is part of a school action research project that was carried out in two cycles (planning, action, observing, and reflecting). The instruments such as observation sheets and interviews were used. The online learning process was observed. The respondents of this study were science teachers at MTs Negeri 1 Prabumulih. The collected data was then analyzed using descriptive techniques. The findings show that after clinical supervision, teachers' teaching skills in online learning was improved. This study differs from previous studies because it tested teachers' teaching skills in online learning through the use of clinical supervision. This research helps principals and teachers improve teachers' online learning teaching skills in order to produce professional teachers.